Debt Enforcement around the World - Djankov, Simeon; Hart, Oliver; McLiesh, Caralee; Shleifer, Andrei (2012)
Insolvency practitioners from 88 countries describe how debt enforcement will proceed against an identical hotel about to default on its debt. We use the data on time, cost, and the likely disposition of the assets (preservation as a going concern vs. piecemeal sale) to construct a measure of the efficiency of debt enforcement in each country. This measure is strongly correlated with per capita income and legal origin and predicts debt market development. Several characteristics of debt enforcement procedures, such as the structure of appeals and availability of floating charge finance, influence efficiency.